Perancangan Dan Pengukuran Antena Mikrostrip Fleksibel Untuk Pendeteksi Tumor Payudara - Rando Saputra; Yusnita Rahayu; Yuyu Wahyu (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
In this research, a flexible microstrip antenna using the Coplanar Waveguide feeding technique was applied for breast tumor detection. The antenna is designed and simulated using HFSS 15.0 simulation software and operates at frequency of 4-6 GHz with a wide bandwidth which is 3.5 GHz (5.5 GHz - 9 GHz). The flexible microstrip antenna using a flexible PET (polyethylene) substrate has a value of εr = 3 and a thickness of 0.135 mm is printed with silver ink as a patch and ground material. The antenna was measured by simulation using breast phantom, and an additional 1 mm of tumor as a comparison of the measurement result. The return loss result from measurement using breast phantom with tumor are -29 dB at frequency of 4.9 GHz, and measurement for breast phantom without tumor are -31.5 dB at frequency of 4.5 GHz. For the bandwidth obtained, both of them get a width of 2 GHz (3.6 GHz - 5.6 GHz). Keywords: Flexible Microstrip Antenna, Bandwidth, Coplanar Waveguide, Polyethylene